Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1145/3328910
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Stage Receptivity Model for Mobile Just-In-Time Health Intervention

Abstract: A critical aspect of mobile just-in-time (JIT) health intervention is proper delivery timing, which correlates with successfully promoting target behaviors. Despite extensive prior studies on interruptibility, however, our understanding of the receptivity of mobile JIT health intervention is limited. This work extends prior interruptibility models to capture the JIT intervention process by including multiple stages of conscious and subconscious decisions. We built BeActive, a mobile intervention system for pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 60 publications
1
50
0
Order By: Relevance
“…As stated earlier, we made an eort to understand and model knowledge workers' responsiveness to the questions related to their work engagement/challenge, and their attentional states. As seen in a very recent study [13], focus level of users can be eective on perception of the mobile notications and adherence to health interventions sent via mobile phones. In this regard, we carried out a data collection study among oce workers capturing their in-situ engagement/challenge levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As stated earlier, we made an eort to understand and model knowledge workers' responsiveness to the questions related to their work engagement/challenge, and their attentional states. As seen in a very recent study [13], focus level of users can be eective on perception of the mobile notications and adherence to health interventions sent via mobile phones. In this regard, we carried out a data collection study among oce workers capturing their in-situ engagement/challenge levels.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the duration of Facebook use and e-mail/calendar use are negatively related to engagement levels, whereas face-to-face interaction are positively related. A very recent work [13] investigated the eects of focus on the adherence to physical activity. They found that when individuals have a high focus on the ongoing task, they are less likely to notice the mobile intervention, or comply with the intervention.…”
Section: Work Engagement and Challenge Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…JITAI relies strongly on the concepts of states-of-vulnerability, i.e., moments with increased risk of negative health outcomes when a participant needs an intervention, and states-of-receptivity, i.e., moments where a person is able to receive, process, and use the intervention provided. In the UbiComp and HCI communities, there has been a growing research in sensing vulnerable conditions (like stress [25,45,46] and depression [44,67]), and understanding receptivity to interventions [11,39,47,59].…”
Section: Just-in-time Adaptive Interventionsmentioning
confidence: 99%